Simple heuristics in a social world - Hertwig, Ralph; Hoffrage, Ulrich; ABC Research Group (Oxford : Oxford University Press, 2013)
This title invites readers to discover the simple heuristics that people use to navigate the complexities and surprises of environments populated with others.
Series from CIP print record.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Interpersonal relations; Social psychology; Heuristic